Insights into the effects of environmental contaminations on olfactory toxicity in fish: A latest review - Tengzhou Li; Bin Liu; Chengzhuang Chen; Ling Liu; Ping Li; Zhi-Hua Li (Environmental Chemistry and Ecotoxicology, 2025)
Fish olfaction is one of the most important senses for sensing information about the surrounding environment. Pollutants in aquatic ecosystems can induce olfactory toxicity and behavioral disturbances in fish. This potentially compromises their survival and affects population stability. In this review, we provide a comprehensive overview of the research history on olfactory toxicity in fish and explore the potential mechanisms of olfactory toxicity induced by environmental pollutants from different aspects of olfactory signal transduction, transmission, and processing in fish. Additionally, the review summarizes the common methods and emerging technologies used in fish olfactory toxicity research in recent years. It also proposes a framework for olfactory toxicity research based on the Adverse Outcome Pathway (AOP), which aims to provide a theoretical basis for the rapid assessment of pollutant-induced olfactory toxicity. Finally, this review analyzes the possible shortcomings of current fish olfactory toxicity studies and provides insights for future research directions.